2020
DOI: 10.1002/cam4.3486
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance and carcinogenic mechanism of pan‐cancer gene POU5F1 in liver hepatocellular carcinoma

Abstract: Background The prognostic and clinicopathological significance of POU Class 5 Homeobox 1 (POU5F1) among various cancers are disputable heretofore. The diagnostic value and functional mechanism of POU5F1 in liver hepatocellular carcinoma (LIHC) have not been studied thoroughly. Methods An integrative strategy of meta‐analysis, bioinformatics, and wet‐lab approach was used to explore the diagnostic and prognostic significance of POU5F1 in various types of tumors, especial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 87 publications
(123 reference statements)
0
24
0
Order By: Relevance
“…These findings may provide a novel direction for seeking a better understanding of risk factors affecting the prognosis of HCC. Published literature has shown that the pathogenic process of genes can be explored by comparing the correlation between the expression of genes and the abundance of different immune cells ( 26 ). High expression of macrophages in the parenchyma can mediate the proliferation, migration, and invasion of tumor cells through a variety of molecular mechanisms, and macrophages infiltration is closely correlated with cancer patient prognosis and therapeutic effects ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may provide a novel direction for seeking a better understanding of risk factors affecting the prognosis of HCC. Published literature has shown that the pathogenic process of genes can be explored by comparing the correlation between the expression of genes and the abundance of different immune cells ( 26 ). High expression of macrophages in the parenchyma can mediate the proliferation, migration, and invasion of tumor cells through a variety of molecular mechanisms, and macrophages infiltration is closely correlated with cancer patient prognosis and therapeutic effects ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…POU5F1 functions as a transcription factor that can activate their downstream genes through binding to the octameric sequence motif. Previous studies showed that the POU5F1 is a pan-cancer gene for various cancers and indicated that POU5F1 is functionally carcinogenic in HCC [33]. EGR1 can be rapidly and transiently induced in response to several stimuli, including growth factors, cytokines, and mechanical stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a significant factor affecting the health and longevity of people worldwide, with nearly 20 million new cancer cases and nearly 10 million deaths reported worldwide in 2020 [ 19 ]. Pan-cancer analysis can identify the similarities and differences in the tumour genomes and provide helpful information for cancer diagnosis and treatment [ 20 ]. In the present study, we evaluated the efficacy of QPRT for pan-cancer analysis.…”
Section: Discussionmentioning
confidence: 99%